Screening and phenotypic identification of auxin-resistant root system mutants in rice (Oryza sativa L.) - ZHANG Zhichang; PAN Weihuai; YAN Xu; YIN Shoupeng; CHENG Zhukuan; PAN Jianwei (浙江大学学报. 农业与生命科学版, 2018)
According to the inhibitory effect of exogenous auxin analog (2,4-dichlorophenoxyacetic acid, 2,4-D) treatment on primary root growth, 188 independent candidate mutant lines were screened out from 60Co-γ mediated radiation mutagenesis pool in rice (Oryza sativa L.) cultivar “Huang Huazhan”. After secondary screening and identification, four auxin-resistant root mutant lines were finally confirmed and designated as Osarr1-1 (Oryza sativa auxin resistant root 1-1), Osarr2-1, Osarr3-1, and Osarr3-2 mutants; among them, the Osarr3-2 was segregated from the Osarr3-1 mutant population and displayed albino seedling phenotype. The results showed that, in the absence of 2,4-D, the number of adventitious roots in Osarr3-1 was significantly higher than that in the wild type, whereas other mutants had similar number of adventitious roots with the wild type. Except the Osarr1-1 mutant exhibited shorter adventitious root phenotype, the others were similar to the wild type. The lateral root number of Osarr3-1 was more than that of the wild type, whereas Osarr3-2 was less; the other mutants were parallel to the wild type. Lateral root elongation of Osarr1-1 and Osarr3-2 was less than the wild type, whereas the other two mutants were similar to the wild type. Under the treatment of 2,4-D, the number and elongation of adventitious roots in these four types of mutants were all significantly higher than the wild type; except for the Osarr3-2, all the other mutants displayed higher lateral root numbers relative to the wild type. Furthermore, the lateral root elongation of all the mutants was much higher than the wild type. The above results show that the root system, including primary root, lateral roots, and adventitious roots in the obtained mutants, displays higher auxin resistance, which provides good genetic resources for deeply revealing regulation mechanism of root growth and development in rice.